Placental Malaria Parasitization at Delivery: Experience at a Nigerian Tertiary Hospital - P.W., Oweisi; C.T., John; J.E., Omietimi; E.O.S., Aigere; D.O., Allagoa; E.L., Kotingo (European Scientific Journal, ESJ, 2018)
Background: In malaria endemic areas, pregnant women are constantly at risk of repeated malaria infestation which if left untreated, poses a significant threat to the health and survival of the mother and her baby. Objective: This study determined the prevalence and risk factors for placental malaria parasitaemia among parturients at the Federal Medical Centre, Yenagoa, Nigeria. Methodology: A prospective cross-sectional analytical study of 205 parturients recruited consecutively at presentation for delivery. An interviewer-administered questionnaire was used to collect data. After delivery, placental blood was collected for microscopy to detect malaria parasites. Data was analysed using SPSS version 22. Results: The prevalence of placental malaria parasitaemia was 13.7%. Maternal age <25 years (P<0.001), low educational status (P = 0.03), low parity (P = 0.03), unbooked status (P < 0.001) and non-use of intermittent preventive treatment (P <0.001) were significantly associated with placental malaria parasitaemia. Receiving three or more doses of sulphadoxine-pyrimethamine for intermittent preventive treatment of malaria in pregnancy was by far, more protective for placental malaria than receiving 2 doses (odds ratio = 0.25). Plasmodium falciparum was the only parasite species detected. Conclusion: Malaria still ravages our obstetric population and the significant contributors include low maternal age, low educational status, low parity, unbooked status and non-use of intermittent preventive treatment in pregnancy. Women should be encouraged to utilize antenatal care. There should be a prompt adoption of the recent WHO recommendations regarding malaria prophylaxis in pregnancy in all obstetric units and the medication should be given as Directly Observed Therapy.